Compliance of Diabetes Mellitus Patients Following Diet Arrangements at IPI Medan Hospital in 2022 - Harahap, Ali Asman; Hutagaol, Aureliya; Harahap, Andi Novi Anri (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Compliance is a patient’s behavior with diet rule which is in accordance with the suggestion of health team. The objective of the research was to find out the compliance of diabetes mellitus patients with following diet control at Hospital IPI, Medan, by using descriptive research design. The samples were 105 respondents, taken by using non-probability sampling technique. The research was conducting in internal disease Polyclinic of Hospital IPI Medan. Based on respondents’ characteristics, it was found that 62 respondents (58.1%) were females, 61.9% of the respondents were 51-60 years old, 39 respondents (37.1%) were Elementary School graduates, 66 respondents (62.9%) suffered from diabetes mellitus type 2, 47 respondents (44.8%) had ideal weight, 52 respondents (49.5%) had suffered from diabetes mellitus for 6 to 10 years, 32 respondents (30.5,5%) suffered Diabetes mellitus plus hypertension. The result of questionnaire about compliance of diabetes mellitus patients with diet rule, it was found that of 100 respondents, 58 of them (55.2%) did not comply. It is recommended that health care providers make a strategy of discipline in controlling diabetes mellitus, especially about diet control in diabetes mellitus. The patients should comply with suggested diet control in order to prevent from complication and the next researchers should do the research on the factors which influence the compliance of diabetes mellitus patients with diet control.